Iodination, Bromination and Isocyanation Reactions of ?-Diketonates of Lanthanum(III), Cerium(IV), Thorium(IV) and Uranyl(VI) - Muthukumar, M.; Balasubramanian, V. (Asian Journal of Chemistry, 2010)
The reactions of coordinate ligands throw light on synthetic methodology to prepare macrocyclic molecules on the basis of template effect. This paper explains iodination, bromination, isocyanation reactions conducted on coordinated β-diketonates of lanthanum(III), cerium(IV) thorium(IV) and uranyl(VI).